Social responsibility journal - Emerald Group Publishing (MCB University Press, 2005)
The journal is interdisciplinary in its scope and encourages submissions from any discipline or any part of the world which addresses any element of the journal's aims. The journal encompasses the full range of theoretical, methodological and substantive debates in the area of social responsibility. Contributions which address the link between different disciplines and / or implications for societal, organisational or individual behavior are especially encouraged.
Keywords: Social responsibility of business : Periodicals; Entreprises : Responsabilité sociale : Périodiques; Publications périodiques; Gouvernance d'entreprise; Responsabilité sociale de l'entreprise; Social responsibility of business